Symbiotic Efficiency, Productivity and Profitability of Soybean as Influenced by Liquid Bio-inoculants and Straw Mulch - Rahangdale, Neha; Kumawat, Narendra; Jadav, M. L.; Bhagat, D. V.; Singh, Mahender; Yadav, R. K. (International Journal of Bio-resource and Stress Management, 2022)
A field experiment was conducted at College of Agriculture (RVSKVV), Indore during kharif (July–October) 2019 to study on physiological parameter, symbiotic efficiency, productivity and profitability of soybean as influenced by liquid bio-inoculants and mulch under Vertisols in relation to ten treatments. Results revealed that the higher growth attributes, physiological parameters and symbiotic parameters were recorded under Rhizobium+phosphours solubilizing bacteria (PSB)+mulch+foliar spray of Plant Growth Promoting Rhizobacteria (PGPR) @ 20 ml l-1 water in comparison to other treatments. The highest seed yield (1232 kg ha-1), straw yield (1537 kg ha-1), protein content (41.72%) and protein yield (51628 kg ha-1) were obtained under Rhizobium+PSB (seed inoculation)+mulch (wheat straw @ 5.0 t ha-1)+foliar spray of PGPR @ 20 ml lml l-1 water (at 35 days and flowering stage), which was at par with Rhizobium+mulch+foliar spray of PGPR @ 10 ml l-1 water, PSB +mulch+foliar spray of PGPR @ 15 ml l-1 water and Rhizobium+PSB +mulch. The maximum gross returns (Rs. 48768 ha-1), net returns (Rs. 20762 ha-1), B:C ratio (1.74), production efficiency (14.0 kg ha-1 day-1) and economic efficiency (Rs. 235.93 ha-1) were also recorded under above treatment. Significantly higher nutrient uptake (82.61 and 35.31 kg N, 4.72 and 8.49 kg P, 24.17 and 41.27 kg K by seed and straw, respectively) were obtained under Rhizobium+PSB+mulch+foliar spray of PGPR @ 20 ml l-1 water.